2006
DOI: 10.1002/acp.1181
|View full text |Cite
|
Sign up to set email alerts
|

Does the presentation of multiple facial composites improve suspect identification?

Abstract: Previous research that has evaluated the accuracy of facial composites has reported low identification rates. Two studies are reported here that consider whether showing more than one composite of the same suspect might improve the rate of identification. Sixteen participant-witnesses saw one of two staged events, each involving a different unfamiliar target. Each participant-witness worked with a police operator to construct a composite of the target they had seen. One, four or eight composites depicting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 10 publications
5
8
0
1
Order By: Relevance
“…In general however, these results are consistent with previous research (e.g. Brace et al, 2006;Bruce et al, 2002) by indicating that presenting more information improves the identification of composites. They are also important from an applied perspective.…”
Section: Targetsupporting
confidence: 91%
See 4 more Smart Citations
“…In general however, these results are consistent with previous research (e.g. Brace et al, 2006;Bruce et al, 2002) by indicating that presenting more information improves the identification of composites. They are also important from an applied perspective.…”
Section: Targetsupporting
confidence: 91%
“…The results also suggest that just presenting more information does not facilitate increased performance at test. Instead, these results provide supporting evidence for the presentation of different types of information, as reported by Brace et al, (2006) and Bruce et al, (2002) The results from Experiment 1 revealed that a three-quarter-view performed as well as a full-face view when all views were presented at study. This is line with face recognition research (e.g.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations